LEGALITY OF COMMUNITY PARTICIPATION IN CROWDFUNDING ACTIVITIES AS A SOURCE OF FUNDING IN VILLAGE-OWNED ENTERPRISES - Azhar, Lucilia Riska; Phahlevy, Rifqi Ridlo (ANTIS PUBLISHER, 2024)
his article reviews the legality of community participation in crowdfunding activities as a source of funding for BUMDes. The focus of this research is on the crowdfunding activity scheme carried out by BUMDes in funding the capital of its business units. This research uses a normative juridical method with a statutory and case approach. Regulations related to crowdfunding activities as a source of funding for BUMDes are regulated in Law No. 9 of 1961; Law No. 25 of 2007; Law No. 6 of 2014 concerning Villages in conjunction with Law No. 3 of 2024; Government Regulation No. 11 of 2021; and Permendesa PDTT No. 3 of 2021. This article uses BUMDes Suwaluh Mandiri Sejahtera as an example of the use of crowdfunding activities in BUMDes. Through this legal framework, BUMDes can utilize crowdfunding activities as an alternative funding that involves active community participation. This research aims to analyze the legality of community participation in crowdfunding activities through community equity participation as a form of funding support to BUMDes.